Sosialisasi SOP Labolatorium Samudra Fitness Center Universitas Samudra - Muhammad, Idrus; Alpidsyah Putra; Muhammad Maulana Fajar; Julio Roberto (Jurnal Pengabdian Keolahragaan dan Sains, 2025)
The fitness laboratory at Samudra University is relatively new and has not been used for teaching and learning activities. The fitness laboratory is one of the facilities provided by the university to improve learning and physical fitness of students and lecturers. Guidelines are needed in a fitness laboratory so that students and the community are more concerned with the equipment used. The existence of a new laboratory is planned to be able to answer the problems that occur in the physical education study program by providing complete equipment and information on the use of equipment. With the information in the fitness laboratory, it is hoped that it can increase the knowledge and awareness of users in using the equipment. Therefore, the author created a title from the problem that occurred, namely the need for SOP (standard operating procedures) for the use of fitness equipment at the Samudra Fitness Center at Samudra University. The method used in implementing this community service is the socialization method to students by explaining the contents of the SOP and the use of equipment. This socialization activity is needed by students and the university to be a reference in an activity. SOP is needed in every activity so that all activities run in a directed and measurable manner. Students are very enthusiastic in participating in this activity of socializing fitness SOP by wanting to participate in other activities for the development of fitness laboratories, one of which is physical training and personal trainer training. Through this activity, students can find out how a fitness laboratory works and students can find out the products in the laboratory.